2020
DOI: 10.1177/2399808320974689
|View full text |Cite
|
Sign up to set email alerts
|

A cost–benefit analysis of implementing urban heat island adaptation measures in small- and medium-sized cities in Austria

Abstract: Urban heat islands are an increasing concern even in small- to medium-sized cities, although these areas are still understudied especially in terms of the economic feasibility of adaptation options. This paper uses adaptation scenarios produced by an urban climate model as inputs to a social cost–benefit analysis in three small- to medium-sized cities in Austria: Mödling, Klagenfurt, and Salzburg. The adaptation scenarios, which consider measures such as increasing the reflectivity of different sealed surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Similar tree planting initiatives are also part of the greening strategies of Delhi (India). EPB is increasingly receiving more papers on urban heat islands, greening and mobility/ infrastructure challenges related to electric vehicles; see, e.g., Johnson et al (2021), Mashhoodi et al (2021), Kamata and Kang (2023) and Jung et al (2024). This trend is likely to continue in the future.…”
Section: The Innovative Role Of Cities In Solving Global Problems Wit...mentioning
confidence: 99%
“…Similar tree planting initiatives are also part of the greening strategies of Delhi (India). EPB is increasingly receiving more papers on urban heat islands, greening and mobility/ infrastructure challenges related to electric vehicles; see, e.g., Johnson et al (2021), Mashhoodi et al (2021), Kamata and Kang (2023) and Jung et al (2024). This trend is likely to continue in the future.…”
Section: The Innovative Role Of Cities In Solving Global Problems Wit...mentioning
confidence: 99%
“…The UHI effect can have detrimental consequences for urban populations, including increased heat-related mortality (Dang, et al, 2018 (Hunt, et al, 2017) depending on the climate of the city, effects of climate change, socio-demographic change, and the approach to valuing reduced mortality (i.e., premature versus displaced deaths; see (Chiabai, et al, 2018). For mitigating UHI effects, cost-benefit analyses of citywide application of green and white solutions are rare; the only published study found BCRs of combined green and white solutions to range between 1.3 and 2.7 for small and medium-size cities in Austria (Johnson, et al, 2020). In the current report, a new analysis for Vienna, Austria, highlighted a positive BCR of 1.8 for green solutions.…”
Section: Extreme Heatmentioning
confidence: 99%
“…Using a social cost-benefit analysis, we showed which measures yielded the largest benefits. I immediately thought of EPB as an ideal place to publish this type of analysis (Johnson et al, 2021), amid a growing number of papers related to climate change. In many ways this brings me back full circle to my original area of study, which was climatology, and my strong awareness of climate change and its potential impacts more than 30 years ago.…”
mentioning
confidence: 99%